High-temperature-resistant Al2O3-SiO2 aerogel composite material as well as normal-pressure drying preparation method and application thereof
The preparation of high-temperature resistant Al2O3-SiO2 aerogel composite material through the normal pressure drying process has solved the problems of high production costs and strict equipment requirements in the existing technology, and achieved low-density, high-strength, high-temperature resistant and excellent thermal insulation properties. It is suitable for large-scale production.
Patent Information
- Application Number
- CN202510084361.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-15
AI Technical Summary
The existing Al2O3-SiO2 aerogel products are prepared by composite fibers combined with supercritical drying technology. The production costs are high, the equipment requirements are strict, and the product size is limited by the equipment, which poses a risk of a high temperature and high pressure environment.
A preparation method for atmospheric drying is proposed. By mixing Al2O3 sol and SiO2 sol with urea, adding a coagulant to form Al2O3-SiO2 sol, and casting it in a ceramic fiber body, after heating treatment and solvent replacement, soaking with a hydrophobic modification liquid, and finally drying atmospheric pressure to obtain high temperature-resistant Al2O3-SiO2 aerogel composite material.
The preparation of Al2O3-SiO2 aerogel composite material with low density, high strength, high temperature resistance and excellent thermal insulation performance has been achieved, which reduces production costs, simplifies the process flow, avoids the danger of high-temperature and high-pressure environments, and is suitable for continuous and large-scale production.
Smart Images

Figure CN119822783A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogel preparation, and in particular to a high temperature resistant Al2O3-SiO2 aerogel composite material and a normal pressure drying preparation method and application thereof. Background Art
[0002] Nano-aerogels represented by silica have made great achievements in the field of thermal insulation due to their high specific surface area, high porosity, low density and low thermal conductivity. However, due to the weak connection between particles, silica-based aerogels sinter at around 600°C, causing the pore structure to collapse and then densify. Introducing refractory phase alumina into the silica aerogel matrix can help maintain its pore structure at high temperatures.
[0003] Currently, the Al2O3-SiO2 aerogel products in the prior art are all prepared by composite fibers combined with supercritical drying process. This method has high production cost and strict requirements on equipment. The high temperature and high pressure environment generated in the process is extremely dangerous and the product size is limited by the equipment. Summary of the invention
[0004] The main purpose of the present invention is to propose a high-temperature resistant Al2O3-SiO2 aerogel composite material and its normal pressure drying preparation method and application, aiming to provide a simple, easy and low-cost normal pressure preparation process, and to obtain a low-density, high-strength, high-temperature resistant and excellent thermal insulation Al2O3-SiO2 aerogel composite material by simply compounding ceramic fibers.
[0005] In a first aspect, a method for preparing a high temperature resistant Al2O3-SiO2 aerogel composite material by drying at normal pressure comprises the following steps:
[0006] Step S1, mixing Al2O3 sol, SiO2 sol and urea, adding a coagulant to obtain Al2O3-SiO2 sol;
[0007] Step S2, pouring the Al2O3-SiO2 sol into the ceramic fiber body to obtain a fiber-gel composite;
[0008] Step S3, heating the fiber-gel composite;
[0009] Step S4, after solvent replacement, the fiber-gel complex after the heating treatment is immersed in a hydrophobic modification liquid to obtain a modified fiber-gel complex;
[0010] Step S5, drying the modified fiber-gel composite to obtain the high temperature resistant Al2O3-SiO2 aerogel composite material.
[0011] In some embodiments, step S1 comprises:
[0012] Mix the aluminum source, alcohol and water to hydrolyze the aluminum source to obtain Al2O3 sol.
[0013] The silicon source, alcohol, water and catalyst are mixed to hydrolyze the silicon source to obtain SiO2 sol.
[0014] Al2O3 sol, SiO2 sol and urea are mixed and stirred for a preset time, and a coagulant is added to obtain Al2O3-SiO2 sol.
[0015] In some embodiments, in step S1, the aluminum source includes aluminum chloride hexahydrate or aluminum nitrate nonahydrate; the molar ratio of the aluminum source, ethanol, and water is 1: (4-15): (8-20); in the step of hydrolyzing the aluminum source to obtain Al2O3 sol, the hydrolysis temperature is 30-80°C; and / or,
[0016] The silicon source includes at least one of methyl orthosilicate, ethyl orthosilicate, silica sol, and water glass; the alcohol includes at least one of methanol, anhydrous ethanol, isopropanol, and n-butanol; the molar ratio of the silicon source to the alcohol and water is 1:(2-12):(1-10); the catalyst includes one of hydrochloric acid, nitric acid, and acetic acid, and the concentration of the catalyst is 0.1-10 mol / L.
[0017] In some embodiments, in step S1, the molar ratio of the aluminum element in the Al2O3 sol to the silicon element in the SiO2 sol is (0-1):1; the molar ratio of the urea to the aluminum element in the Al2O3 sol is (1-15):1; the preset time is 1-12 hours; the coagulant includes propylene oxide, and the molar ratio of the coagulant to the aluminum element in the Al2O3 sol is (5-20):1.
[0018] In some embodiments, in step S2, the ceramic fiber includes any one of high-silica fiber, quartz fiber, aluminum silicate fiber, alumina fiber, mullite fiber, pre-oxidized silk fiber, and carbon fiber.
[0019] In some embodiments, the step S2 includes pouring the Al2O3-SiO2 sol into the ceramic fiber body and letting it stand for 0.5 to 24 hours to obtain a fiber-gel composite.
[0020] In some embodiments, in step S3, the temperature of the heating treatment is 40-100°C.
[0021] In some embodiments, in step S4, the hydrophobic modification liquid includes n-hexane and a complex, and the complex includes at least one of methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, trimethylchlorosilane, phenyltriethoxysilane, dimethyldichlorosilane, trimethylethoxysilane, trimethylbromosilane, trimethoxysilane, tetramethylsilane, dimethyldimethoxysilane, dimethyldiethoxysilane, hexamethyldisiloxane, bis(trimethylsilyl)acetamide, and hexamethyldisilazane.
[0022] In some embodiments, in step S5, the drying process includes drying in an oven at 60 to 80° C. for 4 to 12 hours, and then drying in an oven at 100 to 180° C. for 4 to 12 hours.
[0023] In a second aspect, the present application provides a high temperature resistant Al2O3-SiO2 aerogel composite material.
[0024] In a third aspect, the present application provides a high temperature resistant Al2O3-SiO2 aerogel composite material as a heat insulation board or heat insulation sheet in a lithium ion battery module.
[0025] In the technical solution of the present application, the preparation method provided is simple, safe, reliable, low-cost, and more conducive to continuous and large-scale production. In the preparation method, the fiber / gel composite obtained by secondary gel strengthening can be directly hydrophobically modified, and a product with good performance can be obtained. Its mechanism is: urea is introduced into the Al2O3-SiO2 sol in advance, and then a coagulant is used to promote the formation of a gel skeleton mainly composed of Al-O-Al, and then heat treatment is performed to promote the decomposition of urea to change the pH of the system. On the one hand, the hydroxyl groups in the gel skeleton are further condensed to form a more complete bridge oxygen network, which strengthens the gel skeleton; on the other hand, the free monosilicic acid or disilicate is induced in situ to condense with the hydroxyl groups on the surface of the gel skeleton to form a "silicon" shell, which changes the surface chemical state, so that it can resist the strong acid and alkali environment during the modification process. In addition, the preparation method does not involve a high temperature and high pressure environment, has low equipment requirements, and is therefore safer and more reliable, has a lower cost, and is not limited in product size, which is beneficial to continuous and large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0027] Figure 1 A schematic diagram of a preparation process provided by an embodiment of the present invention;
[0028] Figure 2 This is a physical picture of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 of the present invention;
[0029] Figure 3A This is a scanning electron microscope microscopic morphology image of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 of the present invention;
[0030] Figure 3B for Figure 3A A magnified image of the scanning electron microscope microscopic morphology;
[0031] Figure 4A This is a SEM image of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 of the present invention after being tested at 1200°C / 2h;
[0032] Figure 4B for Figure 4A A magnified image of the scanning electron microscope microscopic morphology;
[0033] Figure 5 Thermal conductivity diagram of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 of the present invention at different temperatures;
[0034] Figure 6 This is a compressive stress-strain curve of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 of the present invention;
[0035] Figure 7 This is a physical picture of the Al2O3-SiO2 aerogel thermal insulation sheet prepared in Example 2 of the present invention;
[0036] Fig. 8A This is a microscopic morphology of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Comparative Example 1 of the present invention;
[0037] Figure 8B for Fig. 8A An enlarged image of the scanning electron microscope micromorphology. DETAILED DESCRIPTION
[0038] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.
[0039] Nano-aerogels represented by silica have high specific surface area (~1200m 2 / g), high porosity (80-99.8%), low density (0.03-0.5 g / cm 3 ) and low thermal conductivity (0.012-0.020W / m·K), making it a great choice in the field of thermal insulation. However, due to the weak connection between particles, silicon-based aerogel sintering occurs at around 600°C, causing the pore structure to collapse and then densify. Studies have shown that introducing 15-25wt% refractory phase alumina into the silica aerogel matrix can maintain its pore structure up to 1200°C.
[0040] At present, the Al2O3-SiO2 aerogel products in the prior art are all prepared by composite fibers combined with supercritical drying process. This method has high production cost and strict requirements on equipment. The high temperature and high pressure environment generated in the process is extremely dangerous and the size of the product is limited by the equipment. In comparison, atmospheric pressure drying equipment is safe and easy to operate, with low cost and less restrictions on sample shape and size. However, there are few reports on the application of atmospheric pressure drying in Al2O3-SiO2 aerogel series products. The core problem is that after the introduction of more active aluminum elements, the complexes formed are susceptible to nucleophilic attack in strong acid and alkali environments and have poor stability. Therefore, it is impossible to directly perform hydrophobic modification treatment - this process step is essential for obtaining high-performance products through atmospheric pressure drying. One of the solutions derived for this is to directly dry after skeleton strengthening, but it is still difficult to resist capillary shrinkage during the drying process, resulting in high product density and serious performance impairment. The second solution is to immerse the silicone pre-hydrolyzate in the aging stage, change the surface chemical state of the gel by constructing a "core-shell" structure, and then perform hydrophobic treatment. Although this method is effective to a certain extent, the process is too complicated and not conducive to industrial production. Therefore, developing a simple, low-cost atmospheric pressure preparation process to obtain low-density, high-strength, high-temperature resistant and excellent thermal insulation Al2O3-SiO2 aerogel composites by simply compounding ceramic fibers is of great significance for expanding the large-scale application of aerogels in the field of ultra-high temperature insulation.
[0041] In view of this, first of all, see Figure 1 The embodiment of the present invention provides a method for preparing a high temperature resistant Al2O3-SiO2 aerogel composite material by drying at normal pressure, comprising the following steps:
[0042] Step S1, mixing Al2O3 sol, SiO2 sol and urea, adding a coagulant to obtain Al2O3-SiO2 sol;
[0043] Step S2, pouring the Al2O3-SiO2 sol into the ceramic fiber body to obtain a fiber-gel composite;
[0044] In this step, the Al2O3-SiO2 sol is poured into the ceramic fiber body, and the sol liquid level needs to be slightly higher than the upper surface of the fiber body to form a resin-impregnated fiber body.
[0045] Step S3, heating the fiber-gel composite;
[0046] In this step, the heating treatment is an in-situ alkali-induced secondary gel strengthening. The alkaline environment constructed by the thermal decomposition of urea, on the one hand, induces the hydroxyl groups in the gel skeleton to further condense to form a more complete Al-O-Si network, and on the other hand, promotes the hydrolyzed free monosilicic acid or disilicate to condense with the hydroxyl groups on the surface of the gel skeleton to form a "silicon" shell.
[0047] Step S4, after solvent replacement, the fiber-gel complex after the heating treatment is immersed in a hydrophobic modification liquid to obtain a modified fiber-gel complex, so as to achieve alkylation treatment on the skeleton surface.
[0048] Step S5, drying the modified fiber-gel composite to obtain the high temperature resistant Al2O3-SiO2 aerogel composite material.
[0049] In some embodiments, step S1 comprises:
[0050] Mix aluminum source, ethanol and water to hydrolyze the aluminum source to obtain Al2O3 sol.
[0051] The silicon source, alcohol, water and catalyst are mixed to hydrolyze the silicon source to obtain SiO2 sol.
[0052] Al2O3 sol, SiO2 sol and urea are mixed and stirred for a preset time, and a coagulant is added to obtain Al2O3-SiO2 sol.
[0053] In some embodiments, in step S1, the aluminum source includes aluminum chloride hexahydrate or aluminum nitrate nonahydrate; the molar ratio of the aluminum source, anhydrous ethanol, and water is 1:(4-15):(8-20); in the step of hydrolyzing the aluminum source to obtain Al2O3 sol, the hydrolysis temperature is 30-80°C;
[0054] The silicon source includes at least one of methyl orthosilicate, ethyl orthosilicate, silica sol, and water glass; the alcohol includes at least one of methanol, anhydrous ethanol, isopropanol, and n-butanol; the molar ratio of the silicon source to the alcohol and water is 1:(2-12):(1-10); the catalyst includes one of hydrochloric acid, nitric acid, and acetic acid, and the concentration of the catalyst is 0.1-10 mol / L.
[0055] In some embodiments, in step S1, the molar ratio of the aluminum element in the Al2O3 sol to the silicon element in the SiO2 sol is (0-1):1; the molar ratio of the urea to the aluminum element in the Al2O3 sol is (1-15):1; the preset time is 1-12 hours; the coagulant includes propylene oxide, and the molar ratio of the coagulant to the aluminum element in the Al2O3 sol is (5-20):1.
[0056] In some embodiments, in step S2, the ceramic fiber includes any one of high-silica fiber, quartz fiber, aluminum silicate fiber, alumina fiber, mullite fiber, pre-oxidized silk fiber, and carbon fiber.
[0057] In some embodiments, the step S2 includes pouring the Al2O3-SiO2 sol into the ceramic fiber body and letting it stand for 0.5 to 24 hours to obtain a fiber-gel composite.
[0058] In some embodiments, in step S3, the temperature of the heating treatment is 40-100°C.
[0059] In some embodiments, in step S4, the hydrophobic modification liquid includes n-hexane and a complex, and the complex includes at least one of methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, trimethylchlorosilane, phenyltriethoxysilane, dimethyldichlorosilane, trimethylethoxysilane, trimethylbromosilane, trimethoxysilane, tetramethylsilane, dimethyldimethoxysilane, dimethyldiethoxysilane, hexamethyldisiloxane, bis(trimethylsilyl)acetamide, and hexamethyldisilazane.
[0060] In some embodiments, in step S5, the drying process includes drying in an oven at 60 to 80° C. for 4 to 12 hours, and then drying in an oven at 100 to 180° C. for 4 to 12 hours.
[0061] In a second aspect, the present application provides a high temperature resistant Al2O3-SiO2 aerogel composite material.
[0062] In a third aspect, the present application provides a high temperature resistant Al2O3-SiO2 aerogel composite material as a heat insulation board or heat insulation sheet in a lithium ion battery module.
[0063] The technical solution of this application has at least the following beneficial effects:
[0064] 1. The preparation method provided by the present application is simple, safe, reliable, low-cost, and more conducive to continuous and large-scale production. In the preparation method, the fiber / gel composite obtained by secondary gel strengthening can be directly hydrophobically modified, and a product with good performance can be obtained. Its mechanism is: urea is introduced into the Al2O3-SiO2 sol in advance, and then a coagulant is used to promote the formation of a gel skeleton mainly composed of Al-O-Al, and then heat treatment is performed to promote the decomposition of urea to change the pH of the system. On the one hand, the hydroxyl groups in the gel skeleton are further condensed to form a more complete bridge oxygen network, which strengthens the gel skeleton; on the other hand, the free monosilicic acid or disilicate is induced in situ to condense with the hydroxyl groups on the surface of the gel skeleton to form a "silicon" shell, which changes the surface chemical state, so that it can resist the strong acid and alkali environment during the modification process. In addition, the preparation method does not involve a high temperature and high pressure environment, has low equipment requirements, and is therefore safer and more reliable, has a lower cost, and is not limited in product size, which is beneficial to continuous and large-scale production.
[0065] 2. The Al2O3-SiO2 aerogel thermal insulation composite material prepared by the present invention has excellent comprehensive performance, which is comparable to supercritical drying products. Its excellent performance is shown in (the relevant performance data is from Example 1): First, the fiber / gel composite has a good hydrophobic modification effect after secondary gel strengthening, so that the drying shrinkage is small, making the product density low (0.25g / cm 3 ), high specific surface area (476.23m 2 / g), low thermal conductivity (the thermal conductivity corresponding to 1000°C is 0.087W / m·K); secondly, compared with the existing method, the preparation method can effectively increase the aluminum enrichment (the aluminum-silicon molar ratio in Example 1 is 0.6, and the existing reports are generally 0.1), thereby further improving the temperature resistance of the product. The nanoporous structure of the matrix aerogel can still be retained after treatment at 1200°C / 2h.
[0066] 3. It can effectively prevent the occurrence of thermal runaway of adjacent battery cells and can control the maximum temperature of the center of unexploded battery cells below 176°C.
[0067] The following is a detailed description of the atmospheric pressure drying method for preparing the high temperature resistant Al2O3-SiO2 aerogel composite material provided by the present invention in conjunction with the embodiments. The described embodiments are one embodiment of the present invention, but they should not be understood as limiting the scope of protection of the present invention.
[0068] Example 1
[0069] A method for preparing a high temperature resistant Al2O3-SiO2 aerogel composite material by drying at normal pressure, the preparation process diagram of which is shown in FIG. Figure 1 Example 1 is a mullite fiber reinforced Al2O3-SiO2 aerogel hard insulation board prepared by the method, which has both excellent mechanical properties and excellent thermal insulation properties. The specific preparation process includes the following steps:
[0070] (1) Preparation of Al2O3-SiO2 sol
[0071] Aluminum chloride hexahydrate, anhydrous ethanol, and water were mixed in a molar ratio of 1:8:10 and stirred in a water bath at 50°C for 70 minutes for hydrolysis to obtain Al2O3 sol; tetraethyl orthosilicate: anhydrous ethanol: water were mixed in a molar ratio of 1:5:2 and stirred for 30 minutes, and then 0.1 mol / L hydrochloric acid was added to adjust the pH of the system to 2-3 to obtain a uniform and transparent SiO2 sol; 57.24 g of aluminum sol and 51.47 g of silica sol were taken in a molar ratio of aluminum: silicon = 0.6, and the mixture was stirred for 6 hours; subsequently, 24.02 g of urea was added and stirred until completely dissolved, and then 34.84 g of propylene oxide was quickly added and stirred for 3 minutes to obtain Al2O3-SiO2 sol.
[0072] (2) Composite of aluminum silica sol and fiber
[0073] The Al2O3-SiO2 sol is quickly poured into a mullite fiber body (the apparent density of the fiber body is 0.15 g / cm 3 , size is 150×150×15mm), the sol liquid level should be slightly higher than the upper surface of the fiber body to ensure that the internal pores of the fiber body are completely filled with the sol, and the fiber / sol composite is obtained by impregnation.
[0074] (3) Gel
[0075] The fiber / sol complex is placed for 24 hours to allow the gel to age to obtain a fiber / gel complex.
[0076] (4) In situ alkali-induced secondary gel strengthening
[0077] The fiber / gel composite was transferred to an oven at 60°C for 12 hours. During this period, the thermal decomposition of urea changed the pH in the gel network, thereby inducing secondary condensation of residual hydroxyl groups and free silica in the system in situ and strengthening the gel skeleton.
[0078] (5) Hydrophobic modification
[0079] The fiber / gel composite after secondary gel reinforcement is first replaced with n-hexane for 24 hours, then immersed in a 20v% trimethylchlorosilane (TMCS) / n-hexane solution, left at 60°C for 12 hours, and then the residual TMCS is removed with n-hexane to complete the hydrophobic modification.
[0080] (6) Drying at normal pressure
[0081] The modified fiber / gel composite was placed in a 60°C oven and dried for 8 hours, and then the oven temperature was adjusted to 120°C and dried for 8 hours to obtain a mullite fiber reinforced Al2O3-SiO2 aerogel composite insulation board.
[0082] The density of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 is only 0.25 g / cm 3 , with a specific surface area of up to 476.23m 2 / g.
[0083] The actual picture of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 is as follows Figure 2 As shown, it can be seen that the surface of the product is relatively smooth, with high integrity and no obvious defects.
[0084] The scanning electron microscope microscopic morphology (SEM) of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 is as follows Figure 3A and3B As shown in the figure, it can be seen that the matrix Al2O3-SiO2 aerogel is evenly filled in the pores of the inorganic ceramic fiber, which is conducive to inhibiting gaseous heat conduction. At the same time, the nano-scale aerogel is closely combined with the surface of the micron-sized mullite fiber, showing good interface compatibility. This multi-scale structural composite strategy expands the stress absorption mechanism, thereby improving the mechanical properties of the composite plate.
[0085] The SEM image of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 after being tested at 1200℃ / 2h is as follows Figure 4A and 4B As shown, it can be seen that the mullite fiber network skeleton is still evenly filled with the aerogel matrix without obvious cracks, and the matrix aerogel pore structure is still retained.
[0086] The thermal conductivity of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 at different temperatures is as follows Figure 5 It can be seen that the thermal conductivity of the product at 1000°C is 0.087W / m·K, showing excellent thermal insulation performance.
[0087] The compressive stress-strain curve of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Example 1 is as follows: Figure 6 As shown. It can be seen that the compressive stress-strain curves are all inverted "S" shape and show three deformation stages, namely, the linear elastic region under a small compressive strain (ε<5%), the yield region with slight hardening as the strain increases (5%<ε<25%), and the densification region with inelastic hardening (ε>30%). The compressive strength is determined by the stress value corresponding to the intersection of the tangents of the initial elastic region and the yield region. It can be concluded that the compressive strength of the product obtained in Example 1 is as high as 1.2MPa, and the compression modulus is as high as 14.7MPa.
[0088] Example 2
[0089] Example 2 is an Al2O3-SiO2 aerogel thermal insulation sheet prepared by the method, which is mainly used in lithium-ion power battery modules to delay or block the propagation of thermal runaway. The preparation process includes the following steps:
[0090] (1) Preparation of Al2O3-SiO2 sol
[0091] Aluminum chloride hexahydrate, anhydrous ethanol, and water were mixed in a molar ratio of 1:8:10 and stirred in a water bath at 50°C for 70 minutes for hydrolysis to obtain Al2O3 sol; tetraethyl orthosilicate: anhydrous ethanol: water were mixed in a molar ratio of 1:5:2 and stirred for 30 minutes, and then 0.1 mol / L hydrochloric acid was added to adjust the pH of the system to 2-3 to obtain a uniform and transparent SiO2 sol; 57.24 g of aluminum sol and 51.47 g of silica sol were taken in a molar ratio of aluminum: silicon = 0.6, and the mixture was stirred for 6 hours; subsequently, 24.02 g of urea was added and stirred until completely dissolved, and then 34.84 g of propylene oxide was quickly added and stirred for 3 minutes to obtain Al2O3-SiO2 sol.
[0092] (2) Composite of aluminum silica sol and fiber
[0093] The Al2O3-SiO2 sol is quickly poured into a mullite fiber body (the apparent density of the fiber body is 0.15 g / cm 3 , size is 180×180×2mm), the sol liquid level should be slightly higher than the upper surface of the fiber body to ensure that the internal pores of the fiber body are completely filled with the sol, and the fiber / sol composite is obtained by impregnation.
[0094] (3) Gel
[0095] The fiber / sol complex is placed for 24 hours to allow the gel to age to obtain a fiber / gel complex.
[0096] (4) In situ alkali-induced secondary gel strengthening
[0097] The fiber / gel composite was transferred to an oven at 60°C for 12 hours. During this period, the thermal decomposition of urea changed the pH in the gel network, thereby inducing secondary condensation of residual hydroxyl groups and free silica in the system in situ and strengthening the gel skeleton.
[0098] (5) Hydrophobic modification
[0099] The fiber / gel composite after secondary gel reinforcement is first replaced with n-hexane for 24 hours, then immersed in a 20v% trimethylchlorosilane (TMCS) / n-hexane solution, left at 60°C for 12 hours, and then the residual TMCS is removed with n-hexane to complete the hydrophobic modification.
[0100] (6) Drying at normal pressure
[0101] The modified fiber / gel composite was placed in a 60°C oven and dried for 8 hours, and then the oven temperature was adjusted to 120°C and dried for 8 hours to obtain a mullite fiber reinforced Al2O3-SiO2 aerogel composite insulation board.
[0102] The actual picture of the Al2O3-SiO2 aerogel insulation sheet prepared in Example 2 is as follows Figure 7 As shown, the product has a high degree of integrity, but it shrinks slightly in the thickness direction after drying, and is only 1.25mm thick. The aerogel insulation sheet was used to verify the thermal runaway propagation experiment of a 63Ah, 100% charged soft-pack 811 battery cell. The results show that the product can effectively block the occurrence of thermal runaway of adjacent batteries and can control the maximum temperature of the center of the unexploded battery cell below 176°C.
[0103] Example 3
[0104] The difference between this embodiment and embodiment 1 is that the amount of urea added in this embodiment is different. In this embodiment, the molar ratio of urea to the aluminum element in the Al2O3 sol is 15:1.
[0105] Example 4
[0106] The difference between this embodiment and embodiment 1 is that the molar ratio of aluminum:silicon in this embodiment is different. In this embodiment, the molar ratio of aluminum:silicon=1:1.
[0107] Comparative Example 1:
[0108] This comparative example uses a post-immersion alkaline solution to induce the gel to undergo secondary cross-linking and strengthening, and the preparation process includes the following steps:
[0109] (1) Preparation of Al2O3-SiO2 sol
[0110] Aluminum chloride hexahydrate, anhydrous ethanol, and water were mixed in a molar ratio of 1:8:10 and stirred in a water bath at 50°C for 70 minutes for hydrolysis to obtain Al2O3 sol; tetraethyl orthosilicate: anhydrous ethanol: water were mixed in a molar ratio of 1:5:2 and stirred for 30 minutes, and then 0.1 mol / L hydrochloric acid was added to adjust the pH of the system to 2-3 to obtain a uniform and transparent SiO2 sol; 57.24 g of aluminum sol and 51.47 g of silica sol were taken in a molar ratio of aluminum: silicon = 0.6, and the mixture was stirred for 6 hours; then 34.84 g of propylene oxide was added and stirred for 3 minutes to obtain Al2O3-SiO2 sol.
[0111] (2) Composite of aluminum silica sol and fiber
[0112] The Al2O3-SiO2 sol is quickly poured into a mullite fiber body (the apparent density of the fiber body is 0.15 g / cm 3 , size is 150×150×15mm), the sol liquid level should be slightly higher than the upper surface of the fiber body to ensure that the internal pores of the fiber body are completely filled with the sol, and the fiber / sol composite is obtained by impregnation.
[0113] (3) Gel
[0114] The fiber / sol complex is placed for 24 hours to allow the gel to age to obtain a fiber / gel complex.
[0115] (4) Post-immersion in alkaline solution to induce secondary cross-linking and strengthening of the gel
[0116] First, 24.02 g of urea was weighed into 86.78 g of water. After the urea was completely dissolved, the fiber / gel composite was completely immersed in the urea aqueous solution, and then transferred to a 60° C. oven and allowed to stand for 12 h.
[0117] (5) Hydrophobic modification
[0118] The fiber / gel composite after secondary gel reinforcement is first replaced with n-hexane for 24 hours, then immersed in a 20v% trimethylchlorosilane (TMCS) / n-hexane solution, left at 60°C for 12 hours, and then the residual TMCS is removed with n-hexane to complete the hydrophobic modification.
[0119] (6) Drying at normal pressure
[0120] The modified fiber / gel composite was placed in a 60°C oven and dried for 8 hours, and then the oven temperature was adjusted to 120°C and dried for 8 hours to obtain a mullite fiber reinforced Al2O3-SiO2 aerogel composite insulation board.
[0121] The microscopic morphology of the mullite fiber composite Al2O3-SiO2 aerogel insulation board prepared in Comparative Example 1 is as follows: Fig. 8A and 8B As shown, it can be seen that there are many macro cracks between the aerogel matrix and the fibers, and the matrix aerogel pore structure has shrunk severely. This is because for composite panels, the external alkaline solution has a large diffusion resistance into the surface, and it is difficult to achieve complete replacement, so the secondary strengthening effect is very limited, that is, the gel is formed and then immersed in urea solution. Furthermore, the thermal conductivity test results show that its room temperature thermal conductivity is as high as 0.047W / m·K. Combined with the results of Example 1, it can be seen that the method of the present invention and the prepared materials have obvious advantages.
[0122] Comparative Example 2:
[0123] The difference between this comparative example and Example 1 is that urea is not added in step (1), and the other processes are the same as Example 1. As a result, in the subsequent step (4) of hydrophobic modification, the gel filled in the fiber body is rapidly dissolved and lost in an acidic environment, and separated from the fiber skeleton, and ultimately a successful product is not obtained.
[0124] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A method for preparing a high temperature resistant Al2O3-SiO2 aerogel composite material by drying at normal pressure, characterized in that: The following steps are involved: Step S1, mixing Al2O3 sol, SiO2 sol and urea, adding a coagulant to obtain Al2O3-SiO2 sol; Step S2, pouring the Al2O3-SiO2 sol into the ceramic fiber body to obtain a fiber-gel composite; Step S3, heating the fiber-gel composite; Step S4, after solvent replacement, the fiber-gel complex after the heating treatment is immersed in a hydrophobic modification liquid to obtain a modified fiber-gel complex; Step S5, drying the modified fiber-gel composite to obtain the high temperature resistant Al2O3-SiO2 aerogel composite material.
2. The atmospheric pressure drying preparation method according to claim 1, characterized in that: The step S1 comprises: Mix the aluminum source, alcohol and water to hydrolyze the aluminum source to obtain Al2O3 sol. The silicon source, alcohol, water and catalyst are mixed to hydrolyze the silicon source to obtain SiO2 sol. Al2O3 sol, SiO2 sol and urea are mixed and stirred for a preset time, and a coagulant is added to obtain Al2O3-SiO2 sol.
3. The atmospheric pressure drying preparation method according to claim 2, characterized in that: In the step S1, the aluminum source includes aluminum chloride hexahydrate or aluminum nitrate nonahydrate; the molar ratio of the aluminum source, alcohol, and water is 1:(4-15):(8-20); in the step of hydrolyzing the aluminum source to obtain Al2O3 sol, the hydrolysis temperature is 30-80°C; and / or, The silicon source includes at least one of methyl orthosilicate, ethyl orthosilicate, silica sol, and water glass; the alcohol includes at least one of methanol, anhydrous ethanol, isopropanol, and n-butanol; the molar ratio of the silicon source to the alcohol and water is 1:(2-12):(1-10); the catalyst includes one of hydrochloric acid, nitric acid, and acetic acid, and the concentration of the catalyst is 0.1-10 mol / L; and / or, In the step S1, the molar ratio of the aluminum element in the Al2O3 sol to the silicon element in the SiO2 sol is (0-1):1; the molar ratio of the urea to the aluminum element in the Al2O3 sol is (1-15):1; the preset time is 1-12 hours; the coagulant includes propylene oxide, and the molar ratio of the coagulant to the aluminum element in the Al2O3 sol is (5-20):
1.
4. The atmospheric pressure drying preparation method according to claim 1, characterized in that: In the step S2, the ceramic fiber includes any one of high silica fiber, quartz fiber, aluminum silicate fiber, alumina fiber, mullite fiber, pre-oxidized silk fiber, and carbon fiber.
5. The atmospheric pressure drying preparation method according to claim 1, characterized in that: The step S2 includes pouring the Al2O3-SiO2 sol into the ceramic fiber body and letting it stand for 0.5 to 24 hours to obtain a fiber-gel composite.
6. The atmospheric pressure drying preparation method according to claim 1, characterized in that: In the step S3, the temperature of the heating treatment is 40-100°C.
7. The atmospheric pressure drying preparation method according to claim 1, characterized in that: In the step S4, the hydrophobic modification liquid includes n-hexane and a complex, and the complex includes at least one of methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, trimethylchlorosilane, phenyltriethoxysilane, dimethyldichlorosilane, trimethylethoxysilane, trimethylbromosilane, trimethoxysilane, tetramethylsilane, dimethyldimethoxysilane, dimethyldiethoxysilane, hexamethyldisiloxane, bis(trimethylsilyl)acetamide, and hexamethyldisilazane.
8. The atmospheric pressure drying preparation method according to claim 1, characterized in that: In the step S5, the drying treatment includes drying in an oven at 60 to 80° C. for 4 to 12 hours and then drying in an oven at 100 to 180° C. for 4 to 12 hours.
9. A high temperature resistant Al2O3-SiO2 aerogel composite material prepared by the atmospheric pressure drying preparation method according to any one of claims 1 to 8.
10. An application, characterized in that: The high temperature resistant Al2O3-SiO2 aerogel composite material as claimed in claim 9 is used as a heat insulation board or heat insulation sheet in a lithium ion battery module.